Odpowiedzi

2009-11-22T17:13:40+01:00
A)
x=3-3y
3-3y-y=5

x=3-3y
-4y=2

x=3-3y
y=-½

x=1½
y=-½
2 1 2
2009-11-22T17:18:55+01:00
5y=2
x+y=2⅖
y=2/5
x+2/5=2 2/5
x=2


c 4y-x=6
17y=0
4y-x=6
y=0
0-x=6
x=-6

a) x+3y=3
x-y=5
x=3-3y
x-y=5
x=3-3y
3-3y-y=5
x=3-3y
-4y=2
x=3-3y
y=-1/2
x=3-3*(-1/2)
x=3/2


2x-y=10
x+5y=-17
x=-17-5y
2x-y=10
x=-17-5y
2(-17-5y)-y=10
x=-17-5y
-34-11y=10
x=-17-5y
-11y=44
x=-17-5y
y=-4
x=-17-5(-4)
x=3
2 3 2
Najlepsza Odpowiedź!
2009-11-22T17:21:54+01:00
5y=2 | :5
x+y=2,4

y=0,4
x=2,4-0,4

y=0,4
x=2

4y-x=6
17y=0 |:17

4y-x=6
y=0

x=-6
y=0

a=b
2a+b=9

a=b
2a+a=9

a=b
3a=9|:3

a=b
a=3

b=a
a=3

b=3
a=3

-------------------------------------------
x+3y=3
x-y=5

x+3y=3
x=5+y

5+y+3y=3
x=5+y

4y=-2 |4
x=5+y

y=-½
x=5+(-½)

y=-½
x=4½


2x-y=10
x+5y=-17

2x-y=10
x=-17-5y

34-10y-y=10
x=-17-5y

-11y=44|:(-11)
x=-17-5y

y=-4
x=-17+20

y=-4
x=3








3 4 3